Peculiarities of teaching history in a vocational-pedagogical university - MOSKALENKO, M.; LARIONOVA, M.; DOROZHKIN, Y.; NOVOSELOVA, A.; SAFRONOVICH, I. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This study is performed to improve the methodology of teaching history in a vocational-pedagogical university. In order to enhance the quality of graduate’s training, as the level of knowing history influences the formation of professional competence in students with specialties related to social activities such as pedagogy, management, economics, and several other lines. The article is aimed at examining critical issues of methodism and methodology of teaching history. RESUMEN Este estudio se realiza para mejorar la metodología de enseñanza de la historia en la universidad vocacional-pedagógica. Con el fin de mejorar la calidad de la formación de los graduados, se influye en el nivel de conocimiento de la historia y en la formación de la competencia profesional en los estudiantes con especialidades relacionadas con actividades sociales como la pedagogía, la gestión, la economía y varias otras líneas. El artículo está dirigido a examinar cuestiones críticas metodicas y metodologica de la enseñanza de la historia.